Discrimination exposure and DNA methylation of stress-related genes in Latina mothers. (December 2018) - Santos, Hudson P.; Nephew, Benjamin C.; Bhattacharya, Arjun; Tan, Xianming; Smith, Laura; Alyamani, Reema Abdulrahman S.; Martin, Elizabeth M.; Perreira, Krista; Fry, Rebecca C.; Murgatroyd, Christopher
Highlights: DNA methylation of genes implicated in stress-related disorders predicts discrimination. Discrimination is inversely associated with NR3C1 and BDNF methylation over time. Discrimination is inversely associated with FKBP5 methylation at T1 but not at T2. BDNF data support the hypothesis of discrimination associated neuroplasticity. Abstract: Latina mothers, who have the highest fertility rate among all ethnic groups in the US, are often exposed to discrimination. The epigenetic changes related to this discrimination are largely unknown. This study is the first to explore the relationship between discrimination and DNA methylation of stress regulatory genes in Latinas. Our sample was Latina women (n = 147) with a mean age of 27.6 years who were assessed at 24–32 weeks' gestation (T1) and 4–6 weeks postpartum (T2) and reside in the U.S. Blood was collected at T1, and the Everyday Discrimination Scale (EDS) was administered at T1 and T2. DNA Methylation at candidate gene regions was determined by bisulphite pyrosequencing. Associations between EDS and DNA methylation were assessed via zero-inflated Poisson models, adjusting for covariates and multiple-test comparisons. Discrimination was negatively associated with methylation at CpG sites within the glucocorticoid receptor ( NR3C1 ) and brain-derived neurotrophic factor ( BDNF ) genes that were consistent over time. In addition, discrimination was negatively associated with methylation of a CpG in the glucocorticoid binding protein ( FKBP5 ) at T1 but not at T2. This study underscores associations between discrimination and epigenetic markers of DNA methylation in Latinas that warrant further investigation to better understand the biological pathways and psychopathological effects of discrimination on Latina mothers and their families.